SOSIALISASI GERAKAN MEMASYARAKATKAN MAKAN IKAN (GEMARIKAN) PADA SISWA SEKOLAH DASAR DI ACEH BARAT - Zulfadhli Zulfadhli; Rinawati Rinawati (Jurnal Marine Kreatif, 2018)
Gemarikan is a government program initiated by the Ministry of Maritime Affairs and Fisheries (KKP RI) which aims to motivate people to like to eat fish. In fish there are omega-3s, EFAs, and DHA which are needed for brain development. Early childhood is strongly advised to consume fish to be healthier, smarter and stronger. This activity is carried out on the basis of students still low interest in consuming fish and do not know the benefits. Gemarikan socialization was carried out at the primary school in Kuala Lumpur district of Samatiga, West Aceh district. The method is carried out by lectures and playing fish games. The material presented was: types of consumption fish, benefits and importance of fish consumption, and tips on choosing fresh fish. Students are very happy and pay attention to what is conveyed in the hope that after this activity has finished interest in increasing fish consumption.